ANALISIS PENGARUH BELANJA KESEHATAN TERHADAP DERAJAT KESEHATAN MASYARAKAT DI SULAWESI TENGGARA - Fantriany, Gian Nanda; Syarif, Muhammad; Nur, Syamsir (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
This study aims to: (1) analyze the effect of health spending on infant mortality in Southeast Sulawesi. (2) Analyzing the effect of health spending on maternal mortality in Southeast Sulawesi. (3) analyze the effect of health spending on life expectancy in Southeast Sulawesi. The type of data used in this study is secondary data, including the accountability report of the Southeast Sulawesi Provincial Health Office, the Southeast Sulawesi Provincial Health Office's strategic plan and the Southeast Sulawesi Provincial Health Office's public health accountability report in 200-2020. This study uses a simple linear regression analysis technique using SPSS 22. The results of this study are: (1) Health Expenditure (X) has a negative and insignificant effect on the Infant Mortality Rate (Y1) in Southeast Sulawesi. (2) Health Expenditure (X) has a negative and insignificant effect on the Maternal Mortality Rate (Y2) in Southeast Sulawesi. (3) Health Expenditure (X) has a positive and significant effect on Life Expectancy (Y3) in Southeast Sulawesi.